Metabolic reprogramming and redox adaptation in sorafenib‐resistant leukemia cells: detected by untargeted metabolomics and stable isotope tracing analysis. Issue 1 (4th April 2019) - You, Xin; Jiang, Weiye; Lu, Wenhua; Zhang, Hui; Yu, Tiantian; Tian, Jingyu; Wen, Shijun; Garcia‐Manero, Guillermo; Huang, Peng; Hu, Yumin
Abstract: Background: Internal tandem duplications (ITD) within the juxtamembrane domain of FMS‐like tyrosine kinase 3 (FLT3) represent a poor prognostic indicator in acute myeloid leukemia (AML). Therapeutic benefits of tyrosine kinase inhibitors, such as sorafenib, are limited due to the emergence of drug resistance. While investigations have been conducted to improve the understanding of the molecular mechanisms underlying the resistance to this FLT3 inhibitor, a profile of cell functioning at the metabolite level and crosstalk between metabolic pathways has yet to be created. This study aimed to elucidate the alteration of metabolomic profile of leukemia cells resistant to the FLT3 inhibitor. Methods: We established two sorafenib‐resistant cell lines carrying FLT3/ITD mutations, namely the murine BaF3/ITD‐R and the human MV4‐11‐R cell lines. We performed a global untargeted metabolomics and stable isotope‐labeling mass spectrometry analysis to identify the metabolic alterations relevant to the therapeutic resistance. Results: The resistant cells displayed fundamentally rewired metabolic profiles, characterized by a higher demand for glucose, accompanied by a reduction in glucose flux into the pentose phosphate pathway (PPP); and by an increase in oxidative stress, accompanied by an enhanced glutathione synthesis. We demonstrated that the highest scoring network of altered metabolites in resistant cells was related to nucleotide degradation. A stable isotope tracing experiment was performed and the results indicated a decrease in the quantity of glucose entering the PPP in resistant cells. Further experiment suggested that the inhibition of major enzymes in the PPP consist of glucose‐6‐phosphate dehydrogenase deficiency (G6PD) in the oxidative arm and transketolase (TKT) in the non‐oxidative arm. In addition, we observed that chronic treatment with sorafenib resulted in an increased oxidative stress in FLT3/ITD‐positive leukemia cells, which was accompanied by decreased cell proliferation and an enhanced antioxidant response. Conclusions: Our data regarding comparative metabolomics characterized a distinct metabolic and redox adaptation that may contribute to sorafenib resistance in FLT3/ITD‐mutated leukemia cells.